Tellurium-lead-lithium oxide glass powder for BC battery N-region conductive paste and preparation method of tellurium-lead-lithium oxide glass powder

By mixing tellurium-lead-lithium oxide glass powder with conductive metal of a specific composition, the problems of high-temperature sintering, compatibility and uneven corrosion of glass powder used in BC cell photovoltaic silver paste were solved, and low-temperature sintering and efficient photoelectric conversion were achieved.

CN120794362AActive Publication Date: 2025-10-17JIANGSU RIYU PHOTOVOLTAIC NEW MATERIAL CO LTD

Patent Information

Application Number
CN202510858066.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2025-10-17
Estimated Expiration
2045-06-25

AI Technical Summary

Technical Problem

The existing glass powder used in BC cell photovoltaic silver paste has problems such as high sintering temperature causing damage to cell silicon wafers, poor compatibility with silver powder affecting conductivity and adhesion, and uneven corrosion leading to inconsistent contact resistance.

Method used

A tellurium-lead-lithium oxide glass powder with a specific composition, aTeO2-bPbO-cLi2O-dBi2O3-eWO3-fZnO-gSiO2-hNa2O, is used. By controlling the Pb, Te, Li content and Li/Na ratio, a low-sintering temperature glass powder is prepared and mixed with a conductive metal and an organic carrier to form a conductive slurry for use in the N region of a BC battery.

Benefits of technology

Low-temperature sintering is achieved to reduce the risk of damage to battery silicon wafers, improve the conductivity and adhesion of silver paste, ensure efficient carrier transmission, and enhance the photoelectric conversion efficiency and performance of BC batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120794362A_ABST
    Figure CN120794362A_ABST
Patent Text Reader

Abstract

The invention discloses tellurium-lead-lithium oxide glass powder for BC battery N-region conductive paste and a preparation method of the tellurium-lead-lithium oxide glass powder, and belongs to the field of photovoltaic silver paste. The glass powder is prepared from components with high contents of Pb, Te and Li as follows: aTeO2-bPbO-cLi2O-dBi2O3-eWO3-fZnO-gSiO2-hNa2O, and the glass powder is prepared from components with high contents of Pb, Te and Li; wherein a + b + c + d + e + f + g + h = 1, 0.2 lt; a < lt >; 0.1 1t, 0.4, 0.1 1t; blt; 0.1 1t, 0.4, 0.1 1t; clt; ct; 0.25, 0 lt; dlt; 0.1, 0 lt; lt, lt; 0.1, 0 lt; flt; 0.1, 0 lt; glt; 0.1, 0 lt; hlt; 0.05, a + b > 0.5, and the ratio of c to h is (3-10): 1. Through specific Pb, Te and Li content control and a specific Li / Na ratio, a strong corrosion effect on a poly layer of a battery piece is achieved, more silver ions dissolved in molten glass can be recrystallized on the surface of a silicon wafer, and thus good ohmic contact is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of BC battery, and particularly relates to a tellurium-lead-lithium oxide glass powder for BC battery N area conductive paste and a preparation method thereof. BACKGROUND

[0002] With the increasing demand for clean energy worldwide, the photovoltaic industry has developed rapidly. As a kind of high-efficiency solar cell technology, BC (Back Contact) battery has attracted widespread attention due to its high photoelectric conversion efficiency and aesthetic appearance. In the preparation process of BC battery, photovoltaic silver paste plays a crucial role, and the performance of glass powder as a key component of photovoltaic silver paste directly affects the quality of silver paste and the performance of BC battery.

[0003] Currently, there are some problems in the use of glass powder for BC battery photovoltaic silver paste. For example, the sintering temperature of some glass powders is relatively high, which can easily cause damage to the battery silicon wafer during sintering, affecting the performance and service life of the battery; the compatibility of some glass powders with silver powder is poor, which can reduce the conductivity and adhesion of the silver paste, and further affect the photoelectric conversion efficiency of the battery; in addition, the existing glass powder may not be uniformly etched when etching the silicon nitride layer, resulting in inconsistent contact resistance between the electrode and the silicon wafer, affecting the overall performance of the battery. Therefore, it is urgent to develop a BC battery photovoltaic silver paste glass powder with excellent performance. SUMMARY

[0004] [TECHNICAL PROBLEM]

[0005] BC battery technology is a new type of photovoltaic cell technology. The positive surface of the battery has no grid line obstruction, which maximizes the use of incident light, reduces optical loss, and brings more effective power generation area, and the appearance is also more beautiful. The carriers of BC battery need to be transported horizontally to the back electrode, and the uniformity of the passivation layer is extremely high. The thickness or doping of the passivation layer will cause local composite increase and open-circuit voltage drop. This requires that the silver paste and the passivation layer have good compatibility and matching to ensure efficient transmission of carriers. The contact ability of the conventional back conductive paste in the market is obviously insufficient for the N area of BC battery.

[0006] [TECHNICAL SCHEME]

[0007] In order to solve the above technical problems, the application provides a tellurium-lead-lithium oxide glass powder for BC battery N area conductive paste, the composition of the glass powder is: aTeO2-bPbO-cLi2O-dBi2O3-eWO3-fZnO-gSiO2-hNa2O;

[0008] Wherein, a, b, c, d, e, f, g, h respectively refer to the proportion of the molar amount of each metal oxide relative to the total glass powder molar amount, a+b+c+d+e+f+g+h=1 (I),

[0009] 0.2 < a < 0.4, 0.1 < b < 0.4, 0.1 < c < 0.25, 0 < d < 0.1, 0 < e < 0.1, 0 < f < 0.1, 0 < g < 0.1, 0 < h < 0.05, and a+b>0.5, the ratio of c to h is (3-10):1.

[0010] In an embodiment of the present application, preferably 0.15 < c < 0.20.

[0011] In an embodiment of the present application, the ratio of c to h is specifically selected from 10:1, 9:1, 8:1, 4:1, 3.5:1. In an embodiment of the present application, the ratio of c to h is preferably (8-10):1.

[0012] In an embodiment of the present application, the composition of the glass frit is: 30%-40% TeO2, 20%-30% PbO, 15%-20% Li2O, 6%-8% Bi2O3, 3%-5% WO3, 3%-5% ZnO, 4-10% SiO2, 2%-4% Na2O by mol%.

[0013] In an embodiment of the present application, the composition of the glass frit is: 36% TeO2, 26% PbO, 16% Li2O, 6% Bi2O3, 3% WO3, 3% ZnO, 8% SiO2, 2% Na2O by mol%.

[0014] In an embodiment of the present application, the preparation method of tellurium-lead-lithium oxide glass powder for BC battery N zone conductive paste comprises:

[0015] 1) Convert the molar ratio of the formula to mass ratio, accurately weigh, mix uniformly, and then place in a corundum crucible, use an up-and-down furnace, heat to 1000-1300℃ with a silicon-molybdenum rod for 20-50 minutes, and cold-rolled to obtain a glass sheet;

[0016] 2) Place the glass sheet and 20mm zirconium beads in a 500ml nylon ball mill tank at a mass ratio of 1:6, use a planetary ball mill at 450r / min for 40-90min to pass through a 100 mesh screen to obtain a glass coarse powder;

[0017] 3) Glass coarse powder, 2mm zirconium beads, alcohol are added into 500ml nylon ball mill tank according to the mass ratio of 1:6:3, a planetary ball mill is used to mill for 30-120min at 350r / min, the particle size is tested by a laser particle size analyzer every 30min, and the sample is dried in a vacuum drying box for 3h, and then the sample is passed through a 120 mesh screen to obtain the required inorganic glass powder.

[0018] Preferably, the particle size of the laser particle size analyzer is in the range of 1.2-1.7μm, and Dmax≤8μm.

[0019] The BC battery N region conductive paste provided by the application comprises 88%-92% of conductive metal, 2-8% of the tellurium-lead-lithium oxide glass powder for the BC battery N region conductive paste, and 6%-12% of an organic carrier.

[0020] The conductive metal is one or more of silver, gold, platinum and aluminum, and is preferably silver;

[0021] The organic carrier comprises an organic solvent, a binder, a thixotropic agent, a surfactant and an additive.

[0022] The organic solvent comprises one or more of acetone, terpineol, hexyl carbitol, butyl carbitol acetate, dimethyl adipate glycol ether and butyl carbitol.

[0023] The binder comprises one or more of ethyl cellulose, phenolic resin, polyvinyl butyral, polyethylene resin, polyacrylic acid, polyurethane resin and rosin derivative.

[0024] The thixotropic agent comprises one or more of castor oil derivative, polyamide, polyamide derivative and fatty acid derivative.

[0025] The surfactant comprises one or more of polyethylene oxide, dodecyl amino propionic acid, benzotriazole, polyethylene glycol, silicone oil, lauric acid, oleic acid, capric acid, myristic acid, stearate and palmitate.

[0026] The application provides a preparation method of the BC battery N region conductive paste.

[0027] The organic carrier, the conductive metal powder and the tellurium-lead-lithium oxide glass powder are mixed, and are repeatedly rolled and grinded by a ceramic three-roll mill to obtain the conductive paste.

[0028] The application further provides a BC battery, which is prepared by printing the conductive paste onto the N region of the BC battery by using a battery sheet screen printing machine, and then sintering.

[0029] The application also provides the application of the above-mentioned tellurium-lead-lithium oxide glass powder for the BC battery N area conductive paste, the above-mentioned conductive paste or the above-mentioned BC battery in the photovoltaic solar field.

[0030] Compared with the prior art, the application has the following advantages and effects:

[0031] The glass powder has a low sintering temperature, and good sintering effects can be achieved at 750-850 DEG C, thereby greatly reducing the damage risk of the battery silicon wafer in the sintering process and being beneficial to improving the performance and service life of the battery.

[0032] The application controls the content of Pb, Te and Li and the specific Li / Na ratio, so that the components play a specific synergistic effect, achieve strong corrosion of the poly layer of the battery wafer, make the silver ions dissolved in the glass liquid more recrystallize on the surface of the silicon wafer, effectively improve the conductivity and adhesion of the silver paste, achieve good ohmic contact, and thus improve the photoelectric conversion efficiency of the BC battery. BRIEF DESCRIPTION OF DRAWINGS

[0033] Figure 1 The interface diagrams of the BCN area battery wafer after sintering of the conductive paste of Examples 1-2 and Comparative Examples 1-2 are printed by screen printing. It can be clearly seen that there are many uniformly arranged silver crystals at the interface of Example 1-2, which indicates that the glass powder corrodes the poly layer of the battery wafer, and the silver ions dissolved in the glass recrystallize on the surface of the silicon wafer. There are almost no silver crystals at the interface shown in Comparative Examples 1-2, which indicates that the glass has insufficient corrosion ability for the poly layer, and cannot make a large amount of silver ions recrystallize on the surface of the silicon wafer. DETAILED DESCRIPTION

[0034] It should be noted that the following examples are intended to explain the application in detail, but not to limit the application.

[0035] The application will be further described below in combination with examples.

[0036] In order to provide sufficient corrosion effect on the passivation layer of the BC battery, the inorganic glass powder of the application adopts components with high Pb, Te and high Li: aTeO2-bPbO-cLi2O-dBi2O3-eWO3-fZnO-gSiO2-hNa2O; wherein a+b+c+d+e+f+g+h=1, 0.2

[0037] The particle size level thereof is characterized by a laser particle size instrument, the hemisphere temperature thereof is observed by HSM (high temperature microscope), the Tg glass transition temperature and the Tc initial crystallization temperature thereof are characterized by DSC (differential scanning calorimetry), the slurry viscosity thereof is analyzed by a viscosity instrument, screen printing is performed on a battery piece, and after sintering densification, the contact resistivity pc thereof is tested by TLM (line transmission model) to characterize the corrosion capacity thereof. The photoelectric conversion efficiency thereof is tested by a special BC special printing equipment and IV machine.

[0038] Example 1

[0039] The glass powder formula in Table 1 is converted into mass ratio according to molar ratio, and analytical pure oxide or carbonate with purity greater than 99.9 is used for batching. A shaker is used for uniform mixing, and the mixture is placed in a corundum crucible and put into a lifting furnace. A silicon molybdenum rod is used for heating to 1000°C for 30 min. The glass sheet is taken out and rolled into a glass sheet by a cold rolling machine. The glass sheet and 20 mm zirconium beads are placed in a 500 ml nylon ball mill tank according to a mass ratio of 1:6. A planetary ball mill is used for ball milling at 450 r / min for 60 min to pass through a 100 mesh screen to obtain glass coarse powder. The glass coarse powder, 2 mm zirconium beads, and alcohol are added to a 500 ml nylon ball mill tank according to a mass ratio of 1:6:3. A planetary ball mill is used for ball milling at 350 r / min for 75 min. The mixture is dried in a vacuum drying box for 3 h, and then passed through a 120 mesh screen to obtain inorganic glass powder, which is denoted as TBL-1. The particle size of the glass powder is tested by a laser particle size instrument. The characteristic temperature is tested by differential scanning calorimetry. The hemisphere temperature is tested by HSM. The above data are shown in Table 2.

[0040] The glass powder TBL-1, silver powder (D50 = 1.8), and organic carrier (40 wt% dimethyl adipate glycol ether, 40 wt% tincalby alcohol acetate, 15 wt% ethyl cellulose and butyl carbitol acetate mixture, 2 wt% sodium oleate, 1 wt% polyether modified siloxane, and 2 wt% hydrogenated castor oil) are mixed uniformly according to a ratio of 3.5:87.5:9, and a three-roll mill is used to prepare a conductive paste, which is denoted as YJ-1. The viscosity of the paste is tested by a viscosity instrument, and the results are shown in Table 3. The paste is printed on the N region of a BC battery by a battery piece screen printing machine. Sintering is performed in a chain furnace with a maximum temperature of 790°C. Defects of the battery piece are repaired by a light injection device. The contact resistivity is tested by a TLM device. The photoelectric conversion efficiency is tested by a special device. The results are shown in Table 4.

[0041] Example 2

[0042] The glass powder formulation of Table 1 was accurately weighed in terms of mass ratio from molar ratio, and the raw materials were prepared by using oxide or carbonate with purity of more than 99.9%. The mixture was uniformly mixed by using a shaker, placed in a corundum crucible, and put into a lifting furnace. The silicon-molybdenum rod was heated to 1000°C for 30 min, taken out, and rolled into glass sheet scrap by a cold rolling machine. The glass sheet and 20 mm zirconium beads were placed in a 500 ml nylon ball mill tank in a mass ratio of 1:6, and a planetary ball mill was used to mill at 450 r / min for 50 min to pass through a 100 mesh screen to obtain glass coarse powder. The glass coarse powder, 2 mm zirconium beads, and alcohol were added to a 500 ml nylon ball mill tank in a mass ratio of 1:6:3, and a planetary ball mill was used to mill at 350 r / min for 65 min. The mixture was dried in a vacuum drying oven for 3 h and passed through a 120 mesh screen to obtain inorganic glass powder, which was labeled as TBL-2. The particle size was tested by using a laser particle size analyzer, the characteristic temperature was tested by differential scanning calorimetry, and the half-ball temperature was tested by HSM. The above data are shown in Table 2.

[0043] The glass powder TBL-2 was uniformly mixed with silver powder (D50=1.8) and organic carrier (40wt% dimethyl adipate, 40wt% tincal alcohol acetate, 15wt% ethyl cellulose and butyl carbitol acetate mixture, 2wt% sodium oleate, 1wt% polyether modified silicone, 2% hydrogenated castor oil) in a ratio of 3:88:9, and a three-roll mill was used to prepare a conductive paste, which was labeled as YJ-2. The viscosity was tested by a viscometer, and the results are shown in Table 3. The paste was printed on the BC battery N area by a battery sheet screen printing machine, sintered in a chain furnace with a maximum temperature of 790°C, and the defects of the battery sheet were repaired by a light injection device. The contact resistivity was tested by a TLM device, and the photoelectric conversion efficiency was tested by a special device. The results are shown in Table 4.

[0044] Example 3

[0045] The glass powder formulation of Table 1 was accurately weighed in terms of mass ratio from molar ratio, and the raw materials were prepared by using oxide or carbonate with purity of more than 99.9%. The mixture was uniformly mixed by using a shaker, placed in a corundum crucible, and put into a lifting furnace. The silicon-molybdenum rod was heated to 1000°C for 30 min, taken out, and rolled into glass sheet scrap by a cold rolling machine. The glass sheet and 20 mm zirconium beads were placed in a 500 ml nylon ball mill tank in a mass ratio of 1:6, and a planetary ball mill was used to mill at 450 r / min for 50 min to pass through a 100 mesh screen to obtain glass coarse powder. The glass coarse powder, 2 mm zirconium beads, and alcohol were added to a 500 ml nylon ball mill tank in a mass ratio of 1:6:3, and a planetary ball mill was used to mill at 350 r / min for 65 min. The mixture was dried in a vacuum drying oven for 3 h and passed through a 120 mesh screen to obtain inorganic glass powder, which was labeled as TBL-2. The particle size was tested by using a laser particle size analyzer, the characteristic temperature was tested by differential scanning calorimetry, and the half-ball temperature was tested by HSM. The above data are shown in Table 2.

[0046] Glass powder TBL-3 was mixed with silver powder (D50=1.8), organic vehicle (45wt% dimethyl adipate, 35wt% tincalbyl alcohol acetate, 15wt% ethyl cellulose and butyl carbitol acetate mixture, 2wt% sodium oleate, 1.5wt% polyether modified silicone, 1.5% hydrogenated castor oil) in the ratio of 3.2:88:8.8, and three-roll milled into a conductive paste, noted as YJ-3. The viscosity was tested by viscometer and the results are shown in Table 3. The paste was printed on BC cell N zone by a cell screen printer, sintered in a chain furnace with the maximum temperature of 790°C, the cell defects were repaired by light injection equipment, the contact resistivity was tested by TLM equipment, and the photoelectric conversion efficiency was tested by special equipment, the results are shown in Table 4.

[0047] Example 4

[0048] Referring to Example 1, glass powder TBL-1 was replaced by equal amount of glass powder TBL-4, and other steps were the same as Example 1, a conductive paste was obtained. The viscosity was tested by viscometer and the results are shown in Table 3. The paste was printed on BC cell N zone by a cell screen printer, sintered in a chain furnace with the maximum temperature of 790°C, the cell defects were repaired by light injection equipment, the contact resistivity was tested by TLM equipment, and the photoelectric conversion efficiency was tested by special equipment, the results are shown in Table 4.

[0049] Example 5

[0050] Referring to Example 1, glass powder TBL-1 was replaced by equal amount of glass powder TBL-5, and other steps were the same as Example 1, a conductive paste was obtained. The viscosity was tested by viscometer and the results are shown in Table 3. The paste was printed on BC cell N zone by a cell screen printer, sintered in a chain furnace with the maximum temperature of 790°C, the cell defects were repaired by light injection equipment, the contact resistivity was tested by TLM equipment, and the photoelectric conversion efficiency was tested by special equipment, the results are shown in Table 4.

[0051] Example 6

[0052] Referring to Example 1, glass powder TBL-1 was replaced by equal amount of glass powder TBL-6, and other steps were the same as Example 1, a conductive paste was obtained. The viscosity was tested by viscometer and the results are shown in Table 3. The paste was printed on BC cell N zone by a cell screen printer, sintered in a chain furnace with the maximum temperature of 790°C, the cell defects were repaired by light injection equipment, the contact resistivity was tested by TLM equipment, and the photoelectric conversion efficiency was tested by special equipment, the results are shown in Table 4.

[0053] Example 7

[0054] Referring to Example 1, glass powder TBL-1 is replaced by an equal amount of glass powder TBL-7, and other steps are the same as in Example 1 to obtain a conductive paste. Its viscosity is tested by a viscometer and is shown in Table 3. The paste is printed to the N region of a BC cell by a cell screen printer, sintered in a chain furnace with a maximum temperature of 790°C, and the cell defects are repaired by a light injection device. The contact resistivity is tested by a TLM device, and the photoelectric conversion efficiency is tested by a special device. The test results are shown in Table 4.

[0055] Comparative Example 1

[0056] Referring to Example 1, glass powder TBL-1 is replaced by an equal amount of glass powder TBL-8, and other steps are the same as in Example 1 to obtain a conductive paste. Glass powder TBL-8 does not satisfy the condition of 0.1 < c < 0.25 in aTeO2-bPbO-cLi2O-dBi2O3-eWO3-fZnO-gSiO2-hNa2O. Its performance is tested by the same method as in Example 1.

[0057] Its viscosity is tested by a viscometer and is shown in Table 3. The paste is printed to the N region of a BC cell by a cell screen printer, sintered in a chain furnace with a maximum temperature of 790°C, and the cell defects are repaired by a light injection device. The contact resistivity is tested by a TLM device, and the photoelectric conversion efficiency is tested by a special device. The test results are shown in Table 4.

[0058] Comparative Example 2

[0059] Referring to Example 1, glass powder TBL-1 is replaced by an equal amount of glass powder TBL-9, and other steps are the same as in Example 1 to obtain a conductive paste. Glass powder TBL-9 does not satisfy the condition of a+b > 0.5 in aTeO2-bPbO-cLi2O-dBi2O3-eWO3-fZnO-gSiO2-hNa2O. Its performance is tested by the same method as in Example 1.

[0060] Its viscosity is tested by a viscometer and is shown in Table 3. The paste is printed to the N region of a BC cell by a cell screen printer, sintered in a chain furnace with a maximum temperature of 790°C, and the cell defects are repaired by a light injection device. The contact resistivity is tested by a TLM device, and the photoelectric conversion efficiency is tested by a special device. The test results are shown in Table 4.

[0061] Comparative Example 3

[0062] With reference to Example 1, glass powder TBL-1 is replaced by an equal amount of glass powder TBL-10, and other steps are the same as in Example 1 to obtain the conductive paste. Glass powder TBL-10 does not satisfy the condition that in aTeO2-bPbO-cLi2O-dBi2O3-eWO3-fZnO-gSiO2-hNa2O, 0.1 < c < 0.25, 0 < d < 0.1. Its performance is tested by the same method as in Example 1.

[0063] Its viscosity is tested by a viscometer and shown in Table 3. The paste is printed onto the N region of a BC cell by a cell screen printer, sintered in a chain furnace with a maximum temperature of 790°C, the cell defects are repaired by a light injection device, its contact resistivity is tested by a TLM device, and its photoelectric conversion efficiency is tested by a special device. The test results are shown in Table 4.

[0064] Comparative Example 4

[0065] With reference to Example 1, glass powder TBL-1 is replaced by an equal amount of glass powder TBL-11, and other steps are the same as in Example 1 to obtain the conductive paste. Glass powder TBL-11 does not satisfy the condition that in aTeO2-bPbO-cLi2O-dBi2O3-eWO3-fZnO-gSiO2-hNa2O, 0.1 < c < 0.25, the ratio of c to h is (3-10):1. Its performance is tested by the same method as in Example 1.

[0066] Its viscosity is tested by a viscometer and shown in Table 3. The paste is printed onto the N region of a BC cell by a cell screen printer, sintered in a chain furnace with a maximum temperature of 790°C, the cell defects are repaired by a light injection device, its contact resistivity is tested by a TLM device, and its photoelectric conversion efficiency is tested by a special device. The test results are shown in Table 4.

[0067] Comparative Example 5

[0068] With reference to Example 1, glass powder TBL-1 is replaced by an equal amount of glass powder TBL-12, and other steps are the same as in Example 1 to obtain the conductive paste. Glass powder TBL-12 does not satisfy the condition that in aTeO2-bPbO-cLi2O-dBi2O3-eWO3-fZnO-gSiO2-hNa2O, the ratio of c to h is (3-10):1. Its performance is tested by the same method as in Example 1.

[0069] Its viscosity is tested by a viscometer and shown in Table 3. The paste is printed onto the N region of a BC cell by a cell screen printer, sintered in a chain furnace with a maximum temperature of 790°C, the cell defects are repaired by a light injection device, its contact resistivity is tested by a TLM device, and its photoelectric conversion efficiency is tested by a special device. The test results are shown in Table 4.

[0070] Table 1 Glass powder formulations of Examples 1-7 and Comparative Examples 1-5 (in mol%)

[0071] Glass powder TeO2 [PbO2] Li2O Bi2O3 WO3 ZnO SiO2 Na2O Example 1 TBL-1 36 26 16 6 3 3 8 2 Example 2 TBL-2 30 24 20 6 5 5 8 2 Example 3 TBL-3 32 26 18 8 4 4 6 2 Example 4 TBL-4 32 24 16 8 5 5 8 2 Example 5 TBL-5 36 22 16 8 5 5 4 4 Example 6 TBL-6 32 26 14 6 5 5 8 4 Example 7 TBL-7 36 24 14 6 3 3 10 4 Comparative Example 1 TBL-8 32 22 8 8 10 10 6 4 Comparative Example 2 TBL-9 20 20 20 10 10 5 10 5 Comparative Example 3 TBL-10 36 26 6 16 3 3 8 2 Comparative Example 4 TBL-11 33 22 25 4 3 3 8 2 Comparative Example 5 TBL-12 36 26 12 6 3 3 8 6

[0072] Table 2 Glass powder properties of Examples 1-7 and Comparative Examples 1-5

[0073]

[0074]

[0075] From Table 2, it can be seen that Comparative Example 4, due to the excessive amount of Li, and Comparative Example 5, due to the excessive amount of Na, both result in a sharp rise in the hemisphere temperature of the glass, and poor flowability, while the actual sintering temperature of the BC battery is around 710-730, which makes it impossible to achieve the effect of dissolving silver, thereby resulting in poor contact.

[0076] Table 3 Viscosity of slurry of Examples 1-7 and Comparative Examples 1-5

[0077] 5R 10R 30R 50R Example 1 294 187 77 46 Example 2 271 169 69 44 Example 3 274 177 69 52 Example 4 277 171 66 55 Example 5 291 185 72 58 Example 6 268 166 78 47 Example 7 266 172 65 55 Comparative Example 1 288 185 62 50 Comparative Example 2 271 169 70 53 Comparative Example 3 254 166 81 43 Comparative Example 4 330 201 99 61 Comparative Example 5 300 195 95 59

[0078] Table 4 TLM test results of Examples 1-7 and Comparative Examples 1-5

[0079]

[0080]

[0081] From Table 4, it can be seen that the contact resistivity pc of Examples 1-7 all remain between 0.2-0.6, while the inorganic glass powder of Comparative Examples 1-3 does not meet the formulation conditions, and low Li or low Te+Pb results in insufficient silver dissolving ability of the inorganic glass powder, and insufficient corrosion ability to the poly layer of the silicon wafer, causing the pc value to sharply rise, thereby resulting in a decrease in efficiency. In Comparative Example 4, the excessive amount of Li, and in Comparative Example 5, the low Li / Na ratio, result in a sharp rise in the hemisphere temperature of the glass, and the glass cannot flow at the sintering temperature of the BC battery, nor can it dissolve silver, resulting in a sharp rise in the pc value, and a decrease in efficiency.

[0082] Comparative Example 6

[0083] Referring to Example 1, glass powder TBL-1 is replaced with an equal amount of glass powder TBL-13, and other steps are the same as in Example 1, to obtain a conductive slurry.

[0084] The components of TBL-13 are as follows:

[0085] Glass powder TeO2 [PbO2] Li2O Bi2O3 WO3 ZnO SiO2 Na2O mol % 28 22 28 4 4 3 8 3 wt % 31.3 37.2 5.8 13.2 6.2 1.5 3.5 1.3

[0086] The same method as in Example 1 was used to test its performance. The paste was printed onto the N region of a BC cell by a cell screen printer, sintered in a chain furnace with a maximum temperature of 790℃, the cell defects were repaired by a light injection device, the contact resistivity was tested by a TLM device, and the photoelectric conversion efficiency was tested by a special device. The test results are shown in Table 5.

[0087] Table 5

[0088]

[0089] It can be seen that although TBL-13 is a tellurium-lead-lithium oxide glass powder containing a relatively high content of Te, Pb and Li, the Li content is too high and the Li / Na ratio is too large, and the overall performance of the conductive paste ultimately exhibited is relatively poor.

[0090] Comparative Example 7

[0091] Referring to Example 1, the glass powder TBL-1 was replaced with an equal amount of glass powder TBL-14, and the other steps were the same as in Example 1 to obtain a conductive paste.

[0092] The components of TBL-14 are as follows:

[0093] Glass powder TeO2 PbO2 Li2O Bi2O3 WO3 ZnO SiO2 Na2O CuO AgO mol % 30.5 22.3 4.3 5.4 2.2 16.4 12.3 1.3 2 3.3 wt % 30.3 33.1 0.8 15.8 3.1 8.3 4.6 0.5 1 2.5

[0094] The same method as in Example 1 was used to test its performance. The paste was printed onto the N region of a BC cell by a cell screen printer, sintered in a chain furnace with a maximum temperature of 790℃, the cell defects were repaired by a light injection device, the contact resistivity was tested by a TLM device, and the photoelectric conversion efficiency was tested by a special device. The test results are shown in Table 6.

[0095] Table 6

[0096]

[0097] It can be seen that although the Li / Na ratio in TBL-14 is controlled appropriately, the main component in the glass powder is a tellurium-lead-zinc oxide glass powder containing a relatively high content of Te, Pb and Zn, and more oxide components such as copper oxide and silver oxide are added, and the combination of these components ultimately exhibits a significantly poorer overall performance of the conductive paste than that of Example 1 of the present application.

[0098] Although the present application has been disclosed with reference to the preferred embodiments thereof, it is not intended to limit the present application thereto, as any modification and variation that can come within the spirit and scope of the present application are intended to be included. Therefore, the scope of the present application should be defined by the appended claims.

Claims

1. A tellurium-lead-lithium oxide glass powder for conductive paste in the N-region of BC cells, the composition of the glass material being: aTeO2 - bPbO - cLi2O - dBi2O3 - eWO3 - fZnO - gSiO2 - hNa2O; in, a, b, c, d, e, f, g, h respectively refer to the proportion of the molar amount of each metal oxide relative to the molar amount of the total glass powder, a + b + c + d + e + f + g + h = 1, 0.2 < a < 0.4, 0.1 < b < 0.4, 0.1 < c < 0.25, 0 < d < 0.1, 0 < e < 0.1, 0 < f < 0.1, 0 < g < 0.1, 0 < h < 0.05, and a + b > 0.5, and the ratio of c to h is (3 - 10):

1.

2. The tellurium-lead-lithium oxide glass powder for the conductive paste of the N region of a BC battery according to claim 1, characterized in that: 0.15<c<0.20。 3. The tellurium-lead-lithium oxide glass powder for the conductive paste of the N region of a BC battery according to claim 1, characterized in that: The ratio of c to h is (8 - 10):

1.

4. The tellurium-lead-lithium oxide glass powder for the conductive paste of the N region of a BC battery according to claim 1, characterized in that: The composition of the glass material is as follows in mol%: 30% - 40% TeO2, 20% - 30% PbO, 15% - 20% Li2O, 6% - 8% Bi2O3, 3% - 5% WO3, 3% - 5% ZnO, 4 - 10% SiO2, 2% - 4% Na2O.

5. The tellurium-lead-lithium oxide glass powder for conductive paste in N region of BC battery according to claim 1, characterized in that: The composition of the glass material is as follows in mol%: 36% TeO2, 26% PbO, 16% Li2O, 6% Bi2O3, 3% WO3, 3% ZnO, 8% SiO2, 2% Na2O.

6. A conductive paste for the N region of a BC battery, characterized in that: By weight fraction, it includes 88% - 92% of conductive metal, 2 - 8% of the tellurium-lead-lithium oxide glass powder for conductive paste in the N-region of the BC cell according to any one of claims 1 - 5, and 6% - 12% of organic carrier.

7. The conductive paste for the N region of a BC battery according to claim 6, characterized in that: The conductive metal is one or more of silver, gold, platinum, and aluminum; the organic carrier includes organic solvents, binders, thixotropic agents, surfactants, and additives; the organic solvents include one or more of acetone, terpineol, hexyl carbitol, butyl carbitol acetate, dimethyl adipate glycol ether, and butyl carbitol.

8. The conductive paste for the N region of a BC battery according to claim 7, characterized in that: The binder includes one or more of ethyl cellulose, phenolic resin, polyvinyl butyral, polyethylene resin, polyacrylic acid, polyurethane resin, and rosin derivatives; the thixotropic agent includes one or more of castor oil derivatives, polyamides, polyamide derivatives, and fatty acid derivatives; the surfactant includes one or more of polyethylene oxide, dodecyl aminopropionic acid, benzotriazole, polyethylene glycol, silicone oil, lauric acid, oleic acid, capric acid, myristic acid, stearate, and palmitate.

9. A BC battery, characterized in that: It is to print the conductive paste according to any one of claims 6 - 8 onto the N-region of the BC cell through a cell screen printer, and then sinter.

10. Use of the tellurium-lead-lithium oxide glass powder for conductive paste in the N-region of the BC cell according to any one of claims 1 - 5, the conductive paste according to any one of claims 6 - 8, or the BC cell according to claim 9 in the field of photovoltaic solar energy.

Citation Information

Patent Citations

  • Glass powder composition, conductive silver paste containing same, and solar cell

    CN111302620A

  • Lithium-tellurium silicon binary glass oxide composite system and conductive paste containing same

    CN114180844A

  • Inorganic glass powder composition, inorganic glass powder, conductive paste and application thereof

    CN119930159A

Cited By

  • Glass powder for conductive paste in P region of BC battery

    CN122325123A